2020
DOI: 10.1186/s42077-020-00090-x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine versus intranasal midazolam as pre-anesthetic medication in pediatric age group undergoing adenotonsillectomy

Abstract: Background The pre-operative period is a very stressful event for most of the individuals undergoing surgery especially the pediatric patients. So, relieving their pre-operative anxiety becomes an important concern for an anesthesiologist. Many anesthetic pre-medications are used to relieve this stress response. Of these pre-medications, midazolam and dexmedetomidine are effectively used as sedatives. The present study was planned to compare intranasal dexmedetomidine with intranasal midazolam as a pre-anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The included studies were published from 2011 to 2022, and a total of 1,495 eligible pediatric patients (ages ranged from 1 month to 14 years) were involved in present analysis. The primary outcomes “number of patients with satisfactory separation from parents, number of patients with satisfactory induction or mask acceptance, and patient’s level of sedation” were reported in 17 studies [ 14 21 , 23 26 , 28 – 30 , 32 , 33 ]. And most of studies paid attention on evaluation in midazolam versus dexmedetomidine, only one study focused on comparison between midazolam and clonidine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were published from 2011 to 2022, and a total of 1,495 eligible pediatric patients (ages ranged from 1 month to 14 years) were involved in present analysis. The primary outcomes “number of patients with satisfactory separation from parents, number of patients with satisfactory induction or mask acceptance, and patient’s level of sedation” were reported in 17 studies [ 14 21 , 23 26 , 28 – 30 , 32 , 33 ]. And most of studies paid attention on evaluation in midazolam versus dexmedetomidine, only one study focused on comparison between midazolam and clonidine [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ], Saad BB et al . [ 30 ] and Abusinna RG et al . [ 33 ] demonstrated that both midazolam and dexmedetomidine provided positive sedative effects, and the proportion of patients with satisfactory sedation was also slightly higher in dexmedetomidine group compared to midazolam group (90.48% vs 71.43%, 100.00% vs 91.67%, and 78.00% vs 70.00%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] It has been widely used as a premedication in pediatric patients for procedural sedation and premedication, where it has shown promising results. [ 9 10 11 12 ] Hussain et al have reported in the literature that dexmedetomidine when administered through the nebulization route had reduced stress response to laryngoscopy and intubation. [ 13 ] Thomas D et al also reported that nebulized dexmedetomidine can attenuate the postoperative sore throat in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Young children's minds are traumatized by their fears of the operation room, needles, and being apart from their parents before general anesthesia (1) . Preoperative anxiety increases postoperative pain and causes hemodynamic instability, metabolic side effects, and emerging agitation (2) .…”
Section: Introductionmentioning
confidence: 99%